Adaptive Molecular Evolution of AKT3 Gene for Positive Diversifying Selection in Mammals. (20th May 2020) - Farmanullah,; Hosseini, Seyed Mahdi; Liang, Aixin; Hua, Guohua; Rehman, Zia ur; Talpur, Hira Sajjad; Salim, Mohammad; Ahmad, Saeed; Abulaiti, Adili; Khan, Momen; Safdar, Muhammad; Kakar, Ihsan Ullah; et al.
Abstract : The V-Akt Murine Thymoma Viral Oncogene Homolog 3 (AKT3) gene is of the serine/threonine-protein kinase family and influences the production of milk fats and cholesterol by acting on the sterol administrative area restricting protein (SREBP). The AKT3 gene is highly preserved in animals, and during lactation in cattle, its expression increases. The AKT3 gene is expressed in the digestive system, mammary gland, and immune cells. A phylogenetic investigation was performed to clarify the evolutionary role of AKT3, by maximum probability. The AKT3 gene sequence data of various mammalian species was evident even with animals undergoing breeding selection. From 39 mammalian species studied, there was a signal of positive diversifying selection with Hominidae at 13Q, 16G, 23R, 24P, 121P, 294K, 327V, 376L, 397K, 445T, and 471F among other codon sites of the AKT3 gene. These sites were codes for amino acids such as arginine, proline, lysine, and leucine indicating major roles for the function of immunological proteins, and in particular, the study highlighted the importance of changes in gene expression of AKT3 on immunity.